Dormancy cycling in Arabidopsis seeds is controlled by seasonally distinct hormone-signaling pathways - Footitt, Steven; Douterelo-Soler, Isabel; Clay, Heather; Finch-Savage, William E (Proceedings of the National Academy of Sciences - PNAS, 2011)
Seeds respond to environmental signals, tuning their dormancy cycles to the seasons and thereby determining the optimum time for plant establishment. The molecular regulation of dormancy cycling is unknown, but an extensive range of mechanisms have been identified in laboratory experiments. Using a targeted investigation of gene expression over the dormancy cycle of Arabidopsis seeds in the field, we investigated how these mechanisms are seasonally coordinated. Depth of dormancy and gene expression patterns were correlated with seasonal changes in soil temperature. The results were consistent with abscisic acid (ABA) signaling linked to deep dormancy in winter being repressed in spring concurrent with enhanced DELLA repression of germination as depth of dormancy decreased. Dormancy increased during winter as soil temperature declined and expression of ABA synthesis (NCED6) and gibberellic acid (GA) catabolism (GA2ox2) genes increased. This was linked to an increase in endogenous ABA that plateaus, but dormancy and DOG1 and MFT expression continued to increase. The expression of SNF1-related protein kinases, SnrK 2.1 and 2.4, also increased consistent with enhanced ABA signaling and sensitivity being modulated by seasonal soil temperature. Dormancy then declined in spring and summer. Endogenous ABA decreased along with positive ABA signaling as expression of ABI2, ABI4, and ABA catabolism (CYP707A2) and GA synthesis (GA3ox1) genes increased. However, during the low-dormancy phase in the summer, expression of transcripts for the germination repressors RGA and RGL2 increased. Unlike deep winter dormancy, this represson can be removed on exposure to light, enabling the completion of germination at the correct time of year.